Evaluation of fractional carbon dioxide laser in the treatment of hypertrophic scars - Hamad, Asmaa; El Eslam Shaker, Engi; Abd El Moneim Sarhan, Naglaa; Abd Elnaby Dawoud, Naeim (Tanta Medical Journal, 2021)
Background Scars affect millions of patients and can significantly influence the physical and psychological functions of patients. Hypertrophic scars are raised nodules or plaques that develop as a result of an excessive collagen deposition during the wound healing process. There are several medical and surgical treatments available. Fractional carbon dioxide (CO2) laser is currently emerging as a minimally invasive therapeutic alternative. Aim The aim was to evaluate the effect of fractional CO2 laser in the treatment of hypertrophic scars. Patients and methods This study included 11 patients with hypertrophic scars (skin type III-IV), and their age ranged from 5 to 25 years old, with a mean of 18.27±7.43 years. Each patient received four sessions of treatment with 1-month interval. Final evaluation was performed 1 month after the last session by the opinion of three dermatologists blinded to the study protocol. The Vancouver scar scale and patient satisfaction before and after treatment were assessed. Skin biopsies were obtained before and 1 month after treatment for light microscopic studies. Results All patients showed clinical improvement. There was a statistically significant difference in the Vancouver scar scale between before and after treatment, where P=0.003. Response to treatment was excellent in 18.2%, good in 27.3%, fair in 36.4%, and poor improvement in 18.2% of patients according to dermatologists' assessments. Overall, 27.3% of patients were highly satisfied, 54.5% were satisfied, and 18.2% were slightly satisfied. Patients tolerated the procedure well with minimal adverse effects. Conclusion Fractional CO2 can be an effective modality in the treatment of hypertrophic scars, without serious adverse events.